Analysis of The Actuating of The Rehabilitation Program House is not Unitable in Palembang City - Febrianza, Muhammad; Sutinah, Sutinah (JPAS (Journal of Public Administration Studies), 2020)
This study examines the dimension of drivers in the implementation of the unworthy housing program in Palembang City. Data were analysed using an interactive model which includes three components of the analysis, namely reduction, data presentation, and conclusion drawing. The results showed that based on the planning dimension, the limited amount of budget owned by the government when compared to Mobilization, the socialization carried out was not optimal, the community was quite enthusiastic about participating in the unfit home rehabilitation program in Palembang City by building their own houses. However, development is being carried out quite slowly due to a lack of expertise and due to the busyness of the community making a living. To overcome this, it is necessary to motivate the community to carry out the construction of their houses, including giving wages.